The adventuress [large type] : a Lady Emily mystery - Alexander, Tasha, 1969- (Alexander, Tasha, 1969- Lady Emily mystery., 2016)
Emily and Colin have come to the French Riviera for a joyous occasion -- the engagement of her lifelong friend Jeremy, Duke of Bainbridge, and American heiress Amity Wells. But the merrymaking is cut short with the shocking death of one of the party in an apparent suicide.